MicroRNA‐181b‐5p, ETS1, and the c‐Met pathway exacerbate the prognosis of pancreatic ductal adenocarcinoma after radiation therapy. Issue 3 (March 2017) - Tomihara, Hideo; Yamada, Daisaku; Eguchi, Hidetoshi; Iwagami, Yoshifumi; Noda, Takehiro; Asaoka, Tadafumi; Wada, Hiroshi; Kawamoto, Koichi; Gotoh, Kunihito; Takeda, Yutaka; Tanemura, Masahiro; Mori, Masaki; et al.
Abstract : Preoperative chemoradiation therapy (CRT) for pancreatic ductal adenocarcinoma (PDAC) has emerged as a reasonable strategy that shows good prognostic impact. However, after preoperative CRT, resected specimens show remnant tumor cells, which indicate that some tumor cells had acquired or were selected for resistance to CRT. Recently, two oncological mechanisms, the EMT and the presence of CSCs, were reported to be associated with resistance in various cancers. Previous reports showed that HGF could induce EMT in PDAC cells; moreover, the HGF receptor, c‐Met, was identified as a dominant pancreatic CSC marker. However, the clinical significance of c‐Met expression remains unclear. So, we hypothesized that remnant PDAC tissue after CRT might harbor cells with high c‐Met expression, and these cells may exacerbate patients' prognosis. In the immunohistochemical analysis, we showed that preoperative CRT was significantly associated with high c‐Met expression; moreover, high c‐Met expression was a significant marker of a dismal prognosis. Next, we investigated mechanisms of c‐Met upregulation in PDAC cells. We established GEM‐resistant and radioresistant PDAC cells to analyze the transcriptome involved in c‐Met expression. The microarray data for the established radiation‐resistant PDAC cells indicated miR‐181b‐5p downregulation, which targets ETS1, one of the transcription factors for c‐Met, and it was shown that radiation exposure induced c‐Met expression through ETS1 increase by the suppression of miR‐181b‐5p. These results suggested that targeting these mechanisms may promote the development of a novel multidisciplinary treatment strategy for improving preoperative CRT efficiency. Abstract : Patients with high c‐Met expression exhibited a distinctly shorter survival time than those with low c‐Met expression. c‐Met expression in PDAC was significantly associated with the presence of preoperative CRT. Radiation exposure induced c‐Met expression in PDAC cells by inhibiting miR‐181b‐5p, which released its suppression of the transcription factor, ETS1; in turn, increased ETS1 levels enhanced c‐Met transcription.